Pertimbangan Interaksi Obat dalam Memilih Obat Psikofarmaka pada Pasien HIV dengan Gangguan Mood: Evidence Based Case Report - Putri, Frilya Rachma; Indiastari, Dewi; Surya, Michael; Hanum, Anisa Syahfitri (Majalah Kedokteran Indonesia, 2023)
Introduction: Mood disorders are one of the most common mental disorders in HIV patients. When used for HIV patients with mood disorders, psychiatric drugs might interact with ARVs. The selection of psychiatric drugs for HIV patients needs to be adjusted to avoid side effects due to adverse drug interactions. Objective: To discuss the interactions between psychiatric drugs and HIV ARVs as a consideration for treatment options.Methods: A literature search was conducted through PubMed and Scopus using keywords with the Boolean operator concept. Selected literature reviews a collection of drug interactions between psychiatric drugs for mood disorders and antiretrovirals used for HIV patients.Results: Out of 88 literatures works obtained, 3 of which reviewed the interactions of various psychiatric drugs with antiretrovirals in HIV patients. Psychopharmaceutical and antiretroviral interactions are related to their metabolism by the Cytochrome P450 (CYP450) enzyme. Psychopharmaceutical and antiretrovirals that are metabolized by the same isoenzyme will cause changes in blood plasma levels which then leads to risks of causing side effects.Conclusion: Although there is no ideal drug option for treating mood disorders in HIV patients, SSRIs are still the first choice because of their fewer interactions with antiretrovirals. The antiretrovirals that interacts the most with psychopharmaceutical are those belonging to PI group. It is recommended to avoid drug combinations that cause a lot of interactions and reduce the treatment benefits.